Risk Management Analysis in the Implementation of Educational Programs for Quality Improvement - Mita, Ridha Prama; Rabukit Damanik; Lendra Faqrurrowzi (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze risk management in the implementation of educational programs as an effort to improve educational quality management. The approach used was qualitative research, with data collection techniques through in-depth interviews, observation and documentation studies. The research subjects consisted of principals, teachers, and students, as parties directly involved in the implementation of educational programs at schools. The results indicate that various risks arise in the implementation of educational programs, such as limited facilities, low student participation, high teacher workloads, and a lack of coordination between management and program implementers. Although several mitigation strategies have been implemented, they have not been fully integrated into the overall school management system. Therefore a more systematic and participatory risk management approach is needed to ensure that each potential risk is identified, analyzed, and addressed appropriately. Effective implementation of risk management can support the achievement of educational program objectives and continuously improve educational quality.